2016
DOI: 10.1111/joid.12073
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Gender, and Medical Waiting Rooms: A Kuwaiti Case Study

Abstract: Although the influence of the built environment in healing and the factors that contribute in creating successful healthcare facilities have been prolific research topics, little has been studied on the subject of how different cultures perceive and navigate these spaces. Through ethnographic observation and online survey, this study explores the way people in a gender‐segregated culture, like Kuwait, occupy the waiting rooms at a public hospital in an urban setting. The findings indicate that people in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…There is a relevant academic literature dealing with the history of doctor's offices and their furnishings [7,8]. It is likely, however, that the material being published will interest the experts, whether these experts be those who study the history of interior design [9], or the history of medicine [10]. There is also a developing literature on the additional aspects of the doctor's waiting room, such as design, content, etc., based upon the recognition that the waiting room is not only a place to store people, but also to make their visit 1900 The waiting room of the doctor in 1900 New York is a sight to behold.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relevant academic literature dealing with the history of doctor's offices and their furnishings [7,8]. It is likely, however, that the material being published will interest the experts, whether these experts be those who study the history of interior design [9], or the history of medicine [10]. There is also a developing literature on the additional aspects of the doctor's waiting room, such as design, content, etc., based upon the recognition that the waiting room is not only a place to store people, but also to make their visit 1900 The waiting room of the doctor in 1900 New York is a sight to behold.…”
Section: Discussionmentioning
confidence: 99%
“…Although design decisions cannot wholly control PR, appropriate spatial layout, furniture arrangement, and seating design can help avoid negative feelings about personal space. For example, Figueroa (2016) suggested that chairs with armrests can improve the feeling of personal space because they mark a physical boundary for the user. In addition, researchers suggested that the waiting room should offer different seating arrangements responding to the patients' preferences, including zones to foster eye contact and communication and others to hinder it (Catania et al, 2011;Figueroa, 2016;Lee, 2011).…”
Section: Influences Of Affective Dimensionsmentioning
confidence: 99%
“…Yet, Danaher and Gallan (2016) suggest that the impact of the physical environment on the patient experience still needs further research. Whereas investigators addressed the environmental effects of healthcare facilities on inpatients (Becker & Douglass, 2008;Figueroa, 2016;Laursen et al, 2014;Ulrich et al, 2008), outpatient services have gained relevance in the healthcare industry (Short et al, 2017), opening new research opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…In health-care facilities, culture, expectations and age are known to play a role in regulation of personal space. For instance, Figueroa (2016) found that in Kuwait, patients gather in gender-segregated groups in hospital waiting rooms. Older women are observed to mark their territory more frequently than men in waiting rooms (Camperio and Malaman, 2002).…”
Section: Introductionmentioning
confidence: 99%